Розвиток інституції прийомної сім'ї як форми опіки над дитиною у Польщі (перша половина ХХ ст.) - Ореста Карпенко (Pavlo Tychyna Uman State Pedagogical University, 2015)
У статті розкрито становлення та розвиток інституції прийомної сім'ї, проблему опіки над дитиною у прийомній сім'ї Польщі, еволюцію надання опіки дітям у першій половині ХХ ст. Акцентовано увагу на висвітленні змісту опіки в Конституції Речі Посполитої Польщі (17. 03. 1921 р.). Розкрито вимоги до прийомних сімей та умови, за яких вони можуть надавати опіку, функції Відділу суспільної опіки, Департаменту опіки над дитиною, які здійснювали правове регулювання опіки над дітьми у прийомних сім'ях Польщі. У повоєнний період опіка розвивалася планово, під керівництвом держави, яка значною мірою фінансувала опікунські акції. В статье раскрыты становление и развитие института приемной семьи, проблема опеки над ребенком в приемной семье Польши, эволюционные перемены в предоставлении опеки детям в первой половине ХХ в. Акцентировано внимание на освещении содержания опеки в Конституции Речи Посполитой Польши (17.03.1921 г.). Раскрыты требования к приемным семьям и условия, в которых они могут предоставлять опеку, функции Отдела общественной опеки, Департамента опеки над ребенком, осуществляющих правовое регулирование опеки над детьми в приемных семьях Польши. В послевоенный период опека развивалась планово, под руководством государства, в значительной степени финансировала опекунские акции. The article reveals the process of formation and evolution of the foster family institution, tackles the problem of foster care in Poland, evolving changes in the childcare system in the 1st half of the 20th century. It highlights the meaning of childcare as defined by the Constitution of the Polish State (Rzechpospolita) (of 17.03.1921). On August 16, 1923 the Act on Social Care was adopted and came into effect (Art. 1, Art. 2 Cl. A). It determined the main objectives and scope of social care and childcare, in particular, as well as priority needs for comfortable living, i.e. food, underwear, clothes and footwear; appropriate accommodation with heating and lighting; job search assistance, etc. In addition, it secured children's right to religious, spiritual, mental and physical development as well as assistance in their preparation for further professional activities. The article also discloses the requirements to foster families and preconditions for care provision, functions of the Social Care Department and Childcare Department that used to regulate foster care in Poland at the stated period. Polish scholars J. Matejek, M. Jamrożek, B. Matyjas distinguished the following three stages in the evolution and activities of the abovementioned institution: 1923 - 1926, 1926 - 1934, and 1934 - 1939. According to them the first stage was characterized by absence of specific guidelines on foster families that fell within the jurisdiction of local authorities, demonstrated no considerable progress in childcare or even had negative results. The second stage was peculiar for its territorial experiments on foster care introduced by the Łódź Social Care Department. Encouraging foster families seemed the only viable solution to the problem which childcare institutions were faced with. As the number of abandoned children grew, municipal infant homes were overcrowded and could not increase their admission quotas. Thus, abandoned infants were placed with foster families, as ordered by the Orphan Care Department. The third stage (1934 - 1939) was notable for its dynamic development of foster families all around Poland. In 1934 the Ministry for Social Care authorized foster care. The post-war childcare system was planned and managed by the state which provided financial support for childcare activities.